Linking human resource practices and organisational performance: evidence from small and medium organisatons in Malaysia. - Chandrakantan Subramaniam; Faridahwati Mohd Shamsudin; Hadziroh Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2011)
The present study attempts to provide empirical evidence on the relationship between the four main dimensions of human resource practices and organisational performance, in response to the call by previous scholars that the influence of specific human resource practices on organisational performance need to be further ascertained across different organisational contexts.The dimensions considered in the stuidy are compensation, information sharing, job security and training and development. Toward this end , a survey among 84 small and medium organisations in the central region of peninsular Malaysia was carried out. Self-reported measures were used to obtain data pertaining to human resources practice dimensions and organisational performance.Regression analyses ere run to examine the proposed relationships and it was found taht all dimensions except job security showed positive relationships to organisational performance, as hypothesized. Dicussion on the findings is hifhlighted, so as the implications for practice and future research Limitations of the study are also offered.